The Capital Flow Volatility Spillover in Some Selected African Economies - Kwarah, Abdullahi Murtala; Kaseeram, Irrshad; Rafindadi, Aliyu Sanusi (Finance & Economics Review, 2021)
Purpose: The study conducted an empirical examination of the link between capital flows and exchange rate by examining the relative influence of FDI and FPI on the exchange rates. Method: The study proceeded with the EGARCH model and the data sample covering the period from 1990-2016. The data were subjected to cross-country screening. The screening criteria are such that all the data that constitute capital in all sampled countries must have equal sample sizes. The measurement of capital flow in each of the sampled countries was restricted to two categories capital, namely, foreign portfolio investment (FPI) and foreign direct investment (FDI). Results: The research establishes that the behavior of capital flow volatility spillover of the sample countries' currencies exchange rate differs, with only South Africa's and Morocco's currencies revealing some slight similarity and existence of asymmetric volatility spillover from capital flows to exchange rate. Additionally, the study discloses that capital flows spillover has a considerable effect on exchange rate volatility than harmful spillover. The study also observed that positive shocks associated with capital flow volatility affect exchange rate value in Botswana more than capital outflow. Further positive capital flow spillover impending from capital inflow has a considerable effect on exchange rate volatility than the harmful spillover impending from the capital outflow. Further, the positive capital flow spill over impending from capital inflow significantly affects exchange rate volatility more than the negative spillovers that emanate from the capital outflow. Implications: This suggests that the monetary policy should consider options that can accelerate capital flow into the Moroccan economy. However, in South Africa for any given quantum of capital flow into the economy, the South African Reserve Bank must use instruments to affect stability; otherwise, the currency exchange rate could remain unstable. Thus, capital withdrawals out of the Egyptian economy will create domestic currency instability. Keywords: Spill-over, Foreign Direct Investments (FDI), Portfolio Investments (PI), asymmetric, capital flow volatility, Exchange rate volatility.